HUBUNGAN KOMORBIDITAS DAN PERILAKU TERHADAP TITER ANTIBODI DAN TERPAPAR COVID-19 PASCA VAKSIN ASTRAZENECA DOSIS LENGKAP DI UTA 45 JAKARTA - Lukas, Stefanus; Aldi, Yufri; Diana Laila Ramatillah; Fatma Sri Wahyuni (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
AstraZeneca vaccine has become one of the efforts to overcome the COVID-19 pandemic. This study aims to determine the relationship between the AstraZeneca vaccine and antibody titers and its association with exposure to COVID-19 infection. This study used a retrospective and prospective cohort design with convenience sampling. A total of 102 respondents who had received a complete dose of the AstraZeneca vaccine and were willing to be followed up for 18 months were involved in this study. Sociodemographic data, comorbidity history, lifestyle, and antibody titers were measured at two times: before the first dose and after the second dose of vaccinations. This study found that there was no significant relationship between comorbidities and respondent behavior (smoking and alcohol consumption) with COVID-19 antibody titers. Physical activity (exercise) showed a positive relationship with COVID-19 antibody titers. Respondents who exercised regularly had higher antibody titers than those who did not. There was a positive relationship between comorbidities, smoking, and alcohol consumption with the risk of exposure to COVID-19 infection after vaccination. This study found that physical activity (exercise) can increase COVID-19 antibody titers and provide protection against COVID-19 infection after vaccination.